Effect of Eutrichopodopsis nitens Blanchard on adult longevity and reproduction on Nezara viridula (L.) - Corrêa-Ferreira, Beatriz Spalding; Thomazini, Marcílio J.; Zamataro, Carlos E. (Pesquisa Agropecuaria Brasileira, 1991)
Comparative studies between unparasitized and parasitized Nezara viridula (L.) demonstrated that parasitism by Eutrichopodopsis nitens Blanchard drastically affected adult longevity and reproductive performance, particulary when parasitism occurred on nymphal stages or on early molted adults. Adults of N. viridula parasitized as nymphs or as early adults did not reproduce and longevity was reduced by ca. 16 and 15 days for males and by ca. 30 and 18 days for females, respectively. Females N. viridula parasitized at the seventh day of adult stage showed their fecundity reduced by ca. 58%; however, egg fertility and egg mass size were not significantly affected.